Existing of Vesicular Arbuscular Mycorrhizal on The Corn Field Subjected by Long-term Organic and Inorganic Fertilizers - Yusnaini, Sri (UNIVERSITY OF LAMPUNG, 2009)
Existing of vesicular arbuscular mycorrhizal fungi were investigated in continuously cropped, conventional agro ecosystems which had received annual long-term (4 years) amendments of either manure or inorganic fertilizer. The systems had an identical 4â€“year crops rotation and differed essentially only in the amount and type of fertilizer supplied. Experiment was setup at Taman Bogo, in the vicinity of Probolinggo, East Lampung. The eight farming systems differed mainly in fertilization application. The organic systems were fertilized exclusively with chicken manure (CK), and green manure Glyricidium sp. (GM) 20 Mg ha-1. One conventional system was fertilized with the inorganic fertilizers (IF) (urea 300 kg ha-1, SP 36 200 kg ha-1, and KCl 100 kg ha-1).Â Four proportion combination fertilized organic and inorganic fertilizers i.e combination of 50% CK + 50% IF, 50% GM + 50% IF, 75% CK + 25% IF, and 75% GM + 25% IF.Â Application of chicken manure both exclusively or combination with inorganic fertilizer gave the higher AMF spore number and root colonization than others treatment. The dominant species of AMF at all treatment was Glomus constrictum.